2010
DOI: 10.1177/1938640010379048
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Year Long-Term Retrospective Analysis of the Use of Radiofrequency Nerve Ablation for the Treatment of Neurogenic Heel Pain

Abstract: The authors discuss their rationale for the use of radiofrequency nerve ablation (RFNA) in the treatment of chronic neurogenic heel pain. Patients treated for plantar fasciitis who fail to improve after conservative and/ or surgical treatment should be reevaluated for a coexistent nerve entrapment. The results of a retrospective study of 82 patients who have undergone RFNA are presented. The patients were followed at 5, 10, and 12 years after the procedure. An evaluation of medical records was performed as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In cadaver studies of anatomy, various authors have described the variable anatomy of the tibial nerve and its terminal branches in terms of the location of its bifurcation with respect to the flexor retinaculum . The main variations are the bifurcation of the tibial nerve into the medial and lateral plantar nerves with respect to the retinaculum, bifurcation of the medial calcaneal branch, and bifurcation of the first calcaneal branch.…”
Section: Anatomy and Correlation With Usmentioning
confidence: 99%
“…In cadaver studies of anatomy, various authors have described the variable anatomy of the tibial nerve and its terminal branches in terms of the location of its bifurcation with respect to the flexor retinaculum . The main variations are the bifurcation of the tibial nerve into the medial and lateral plantar nerves with respect to the retinaculum, bifurcation of the medial calcaneal branch, and bifurcation of the first calcaneal branch.…”
Section: Anatomy and Correlation With Usmentioning
confidence: 99%
“…Sollitto et al 27 performed RTL for resistant PF and reported that 92% of the patients experienced a complete resolution of the symptoms. Cozzarelli et al 9 reported a success rate of 89% for radiofrequency nerve ablation (RFNA) in the treatment of chronic neurogenic heel pain at the 5-, 10-, and 12-year follow-ups. Similarly, Cione et al 8 reported a 93.3% success rate of RTL in patients with plantar heel pain with a neurological origin, such as medial calcaneal nerve entrapment or heel neuroma.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic heel pain associated with plantar fasciitis (PF) is one of the most common clinical entities encountered by foot and ankle specialists and affects adults of all ages with either an active or sedentary lifestyle. 9 Within their lifetime, 10% of the general population is expected to present to orthopedic surgeons with heel pain due to degenerative changes in the plantar fascia. 19,20 PF results from the cumulative effect of recurrent microinjuries and chronic damage in the plantar aponeurosis at the insertion of the plantar fascia on the medial process of the calcaneal tuberosity.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic plantar fasciitis and local varicosities represented the findings most frequently associated with entrapment of the abductor digiti quinti nerve. Initially, heel pain should be treated with conservative measures, including the use of a nocturnal orthosis, therapeutic footwear, physical therapy, anti-inflammatory drugs and corticoid infiltration ( 16 , 34 , 35 ) .…”
Section: Discussionmentioning
confidence: 99%
“…As the pain becomes chronic, over a period longer than six month and without any improvement with the conservative treatment, the hypothesis of compression of the first branch of the lateral plantar nerve should be considered. In such cases, the patients may benefit from surgical decompression of the region ( 16 , 35 - 37 ) by endoscopic approach ( 16 , 36 ) , radiofrequency ablation techniques ( 34 ) or open surgery.…”
Section: Discussionmentioning
confidence: 99%